The U.S. Policy of Democracy Promotion in the Post-Soviet Space - V. A. Ponomarev (Проблемы постсоветского пространства)
After the collapse of the USSR, U.S. Administrations exploited the policy of «democracy promotion» to expand American influence in the post-Soviet space and to counterbalance Russia. In the light of the military campaign in Syria, the escalation around Iran, North Korea and Venezuela, the importance of the post-Soviet space for the US foreign policy has declined, U.S. aid to the region was cut. However, the Trump Administration maintains interest in keeping loyal elites in power to ensure the implementation of reforms and business projects, in particular, with a view to export U.S. military equipment and liquefied natural gas. The U.S. primary goal is to counteract Russian influence in the region, to prevent post-Soviet republics from building stronger ties with Moscow and reorient them towards the «collective West».